GLOBAL CLIMATE CHANGE AND SECURITY THREATS - Juraj Kesel; Vladimir Sedlak (European Scientific Journal, ESJ, 2014)
Climate change and the associated particularly pronounced warming of the Earth today represent a serious global environmental threat. The paper presents the issues of climate change as a source of threat to not only the environment but also a source of current security threats. The aim is to point out to climate change, which some forecasts with a negative impact on the environment are now actually happening. The paper focuses on the detection of gradual climate changes that culminate in the final verdict of the IPCC, to the impacts of climate change on the most serious ecosystems with reference to possible security threats such climate changes that may significantly affect the quality or safety of a person or existence of life on Earth.